A Computed Tomographic Assessment of Osteitis of Sinus Bony Structures in Horses With Sinonasal Disorders - Dixon, Padraic M.; Puidupin, Coline; Borkent, Dewi; Liuti, Tiziana; Reardon, Richard J. M. (Frontiers in Veterinary Science, 2020)
Background: Computed tomographic (CT) imaging has shown some horses with sinonasal diseases to have changes in their sinus bony structures. Scintigraphic and clinical evidence of sinus osteitis have also been reported. However, no study has objectively examined for the presence and degree of osteitis in equine sinonasal disease. Objectives: To assess for the presence and extent of osteitis of sinus-related bony structures by examination of CT images of horses with clinically and sinoscopically confirmed unilateral sinonasal disease. Study design: Retrospective examination of CT images of horses with confirmed, mainly chronic (>2 month duration) unilateral sinus disease of different aetiologies. Methods: Bone thickness at designated sites of the maxillary bone (n=3), frontal bone (n=1), infraorbital canal (n=2) and bony nasolacrimal duct (n=1) were measured, as were the maximal diameters of the infraorbital canal and the bony nasolacrimal duct on both affected and control sides. Maxillary bone density (in Hounsfield Units) was also assessed bilaterally. Bone thickness was compared between affected and controlled sides using paired statistical tests. Results: Bone was significantly thicker in the affected sinuses compared to the control sides at the three maxillary bone sites (all, P<0.001) and at both infraorbital bone sites (both, P<0.001), but not at the two most dorsal sites examined, i.e. frontal bone (P=0.188) and bony nasolacrimal duct (P=-0.260) sites. Infraorbital canal and bony nasolacrimal duct diameters were significantly wider in the affected as compared to the control sides (P<0.001 and P=0.002 respectively). Maxillary bone density did not differ significantly between the affected (mean=1075 HU, SD=230.01) and control (mean 1100, SD=200.71) sides (t(58)=-1.03, P=0.306). Main Limitations: Possible variation in selecting measurement sites. Variation in the severity and chronicity of sinonasal disease between horses. Conclusions: Osteitis and enlargement of paranasal bony structures commonly occurs in horses with sinonasal disease and can explain the clinical presence of ipsilateral diffuse soft tissue facial swelling, epiphora and scintigraphic evidence of bone inflammation in sinonasal disease. Osteitis or distortion of the infraorbital canal or maxillary septal bulla may cause difficulty in sinoscopically fenestrating the maxillary septal bulla in horses with sinonasal disease.